Hip and Pelvis Bone Tumors: Can You Make It Simple? - Afonso, P Diana; Weber, Marc-André; Isaac, Amanda; Bloem, Johan L (Seminars in musculoskeletal radiology, 2019)
Although it is possible for any osseous tumor or tumorlike lesion to occur in and around the hip and pelvis, there are preferential lesions. Most tumors share many imaging features with those arising elsewhere in the skeletal system, but some may show specific morphological and imaging features. Furthermore, specific criteria and rules of thumb are related to this anatomical area that radiologists should know, which together with the imaging findings and clinical context will lead to a more confident diagnosis.In this article we review the basic anatomical and imaging principles in the hip and pelvis and their diagnostic criteria, describe the most common regional benign and malignant bone tumors and pseudotumors, and highlight their main imaging features and common differential diagnosis while keep this article as relatively simple and straightforward as possible. Soft tissue tumors are beyond the scope of this article.